Comparison of the Efficacy and Safety of Two Cryotherapy Protocols in the Treatment of Common Viral Warts: A Prospective Observational Study - Jihan M. Muhaidat; Firas A. Al-qarqaz; Diala M. Alshiyab; Hadeel S. Alkofahi; Yousef Khader; Mawaddah Y. Ababneh (Dermatology Research and Practice)
Background. Cryotherapy (freezing by liquid nitrogen) is an effective and widely used method for treatment of common warts. Patients often need multiple sessions at variable intervals. Protocols used by different dermatologists vary in terms of freezing time, the number of cycles, and the intervals between sessions. Aim. To compare the efficacy (cure rates) and safety (complications, early and late) of two cryotherapy treatment protocols for common viral warts. Method. A prospective observational study was conducted; it involved 80 patients with common warts on the hands and feet who were treated with cryotherapy done by two dermatologists who use different protocols; group 1 (45 patients) were treated by a single cycle of 10 seconds of freezing at 2 weekly intervals, and group 2 (35 patients) received a single cycle of 20 seconds of freezing at 4-weeks intervals. The two protocols were compared in terms of cure rate and complications 1-2 months after the final treatment. Recurrence rate and late complications were assessed at 9–12 months after the final treatment. Results. Group 1 patients achieved higher cure rate than group 2, 77.8% and 54.3%, respectively (P=0.001). Early (blistering) and late complications (dyspigmentation and scarring) were comparable in both groups. Pain score associated with protocol 1 (5.2/10) was less than protocol 2 (6.4/10) (P=0.004). Recurrence rate (17%) was comparable in both groups. Association between cure rate and duration of warts (P=0.022) and also association between cure rate and the mean number of warts (P=0.001) were demonstrated. Conclusions. Cryotherapy is an effective and safe treatment for common viral warts of hands and feet. The impact of shorter intervals on cure rate was more significant than increasing freezing time with longer intervals between freezing sessions. The study was approved by the local IRB committee (285-2018).